進路成熟と学業成績・学習態度の関連に関する研究 - 竹内, 登規夫 (進路指導研究, 1987)
The purpose of this study is to examine the effectiveness of career guidance practices through academic subjects by correlating of educational and vocational career maturity with results of academic subjects or attitudes during school hours. In addition, this study is to consider that "learning of career" may facilitate career development of junior high-school students. The result of this study showed that the correlation between educational career maturity and results of academic subjects was significantly. On the other hand , vocational career development and attitudes during hours, revealed no significant. Finally, perhaps most importantly, this study suggested that "learning of career" facilitate career development on educational and vocational dimentions both. Therefore, the approarch to fostering the career development for students, particularly those likely to reinforce career guidance practices through "learning of career" in class activity curriculum.